“Internet+” pharmacy in psychiatric hospital amid COVID-19 and post-pandemic period: analysis and development - Xie, Weiming; Wang, Fei; Qian, Yayun; Qiu, Linghe; Zhou, Qin; Shen, Yuan; Wu, Jianhong (Frontiers in Psychiatry, 2024)
ObjectiveThis study aims to explore the differences in “Internet+” pharmacy prescriptions in psychiatric hospitals before and after the outbreak of the coronavirus disease 2019 (COVID-19) pandemic. It also seeks to examine changes in patient healthcare behaviors in the post-pandemic era and to identify the potential role of “Internet+” pharmacy in improving the current healthcare system.MethodsPrescriptions from the “Internet+” pharmacy at The Affiliated Mental Health Center of Jiangnan University, collected between December 1, 2021, and November 30, 2023, were analyzed. The period was divided into four stages based on the COVID-19 pandemic’s progression in China. Descriptive statistical analysis was conducted on various prescription-related factors, including patient information, prescription type, disease distribution, medication type, frequency of medication use, pharmacist review time, and instances of irrational medication use.ResultsA total of 2914 prescriptions were collected. The male-to-female ratio (MFR) varied significantly across different stages of the epidemic. In the pre-pandemic II period, females represented the highest proportion (66.10%, MFR 0.51), and individuals aged 18-39 made up the majority (56.70%) across all stages. The proportion of psycho-counseling prescriptions was highest in the pre-pandemic II period (76.74%), while the total number of psycho-counseling prescriptions was greatest during the epidemic, with 798 cases. A total of 38 diseases were involved, with depression accounting for the largest proportion (38.98%) at each stage, followed by the highest usage of antidepressants (49.60%). A total of 85 types of medications were used, with quetiapine representing the highest proportion before the epidemic (16.56%, 10.92%), while escitalopram accounted for the highest proportion after the epidemic (10.98%). The majority of patients (70.87%) took medication once daily. 42.23% of pharmacist review times were ≤1 minute, and the mean review time was longest in the post-pandemic period (6175.1 seconds). During the pre-pandemic and epidemic periods, the most common pharmacist review time occurred between 12:00 and 17:59 (41.46%), while in the post-pandemic period, the most common review time was between 18:00 and 23:59 (36.70%). The initial rate of irrational prescriptions was 37.85%. After manual review by pharmacists, the irrational prescription rate of Internet prescriptions decreased to 1.13%.ConclusionThe development of “Internet+” pharmacy has effectively addressed the medical needs of the relevant population and played a crucial role in combating the COVID-19 pandemic. Future advancements should focus on optimizing the allocation of healthcare resources and expanding innovative pharmacy services to broaden the developmental pathways of the ‘Internet+’ pharmacy ecosystem.